Zarządzanie projektami jako narzędzie wspomagające proces globalizacji - Klonowski, Przemysław (The project management as a concept aiding the process of globalization, 2005)
The project management is a tool that facilitates the planning, implementing and monitoring of all the aspects of a project. These actions should aim at achieving three mutually dependent project objectives: certain time, cost and scope of work. The project management knowledge offers a set of leadership techniques and leadership tools for the realization of the most important phases of the project. They are necessary to the efficient performance of a project. Therefore the International Project Management Association has performed the standardization of techniques and methods. They made a logical system aimed at the continuous improvement of relevant actions. The concept of project management helps the leadership of the global projects and the globalization promotes the creation of techniques and methods of the efficient project management. The PM concept is a global concept, because it is standarized. The global attractiveness of project management becomes more important and the reason is the growth of the technical software.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 136-145